FACILITATING THE INVOLVEMENT OF COMMUNITY LEADERS IN THE DEVELOPMENT OF CULTURE-BASED EDUCATION IN MAPPI DISTRICT, SOUTH PAPUA PROVINCE - Bernardinus Agus Arswimba; Eny Winarti; Hendra Michael Aquan; Cecilia Paulina Sianipar; Ignatius Yulius Kristio Budiasmoro (JURNAL NALAR PENDIDIKAN, 2023)
This research analyzed the strategic role of community leaders in developing culture-based education and formulating a social facilitation model for community leaders in improving quality education in Mappi Regency, Papua. This is a qualitative action research. Data collection used Focus Group Discussions (FGD) and data analysis used SWOT analysis. The findings showed that community leaders have a strategic role in culture-based education to preserve cultural values as important social capital for the Mappi younger generation. The main challenges for community leaders include lacking facilities, infrastructure, formal qualifications, and weak coordination. In their involvement in schools, community leaders have opportunities through utilizing school operational assistance funds and guidance from community organizations. In addition, optimizing the role of community leaders required improved coordination, facilities, and affirmative policies. The facilitated engagement model involving community leaders in teaching local skills and knowledge has proven effective in developing culture-based education in schools. The community leader teaching program is considered an important tool to advance culture-based education in Mappi. Schools that have implemented this social facilitation model should continue to be promoted as role models for other schools in integrating Mappi cultural elements into the school curriculum. Keywords: culture-based education, social facilitation model, Mappi cultural education, teaching figures